Musculoskeletal pain and psychosocial factors among Lebanese workers. (19th October 2011) - Habib, Rima R; Frangieh, Maria; Haddad, Nadine; Hojeij, Safaa; Coggon, David
Abstract : Objectives: Epidemiological research has linked musculoskeletal disorders with various physical activities in the workplace, and also with psychosocial influences such as job demand and job dissatisfaction. Studies assessing musculoskeletal pain in different occupational settings are scarce in the Arab world including Lebanon. The study aimed to assess the relation between psychosocial parameters at work and musculoskeletal disorders in a population of nurses, food industry and office workers in Lebanon. Methods: A cross sectional survey of 544 workers was carried out: 168 food industry workers, 186 nurses, and 190 office workers were interviewed using the CUPID questionnaire. Data were collected on socio-demographics, physical and psychosocial characteristics, and workers' general and mental health. Musculoskeletal pain was recorded as pain in any of the lower back, neck, shoulder, elbow, hand/wrist, and knee in the past 12 months. Multiple regression analyses were carried out using SPSS 16. Results: At least 71% within each occupation reported musculoskeletal pain. Job demand, support from colleagues, and time pressure were significant risk factors for musculoskeletal pain. Food industry workers with high job demand were more likely to report musculoskeletal pain (OR=2.4; 95% CI 1.19 to 4.82); nurses who received support from colleagues were less likely to report musculoskeletal pain (OR=0.37; 95% CI 0.15 to 0.90); and male office workers who experienced time pressure were also more likely to report musculoskeletal pain (OR=4.96; 95% CI 1.79 to 11.97). Conclusions: Psychosocial parameters at the workplace are significant risk factors for musculoskeletal pain. This association calls for intervention to improve the social environment in the workplace.